Management practices for multichannel marketing: study on retail consumer goods (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
Multi-channel marketing practices have become more intense in the retail industry, causing benefits and challenges for retailers. This study analyzed the multichannel marketing management practices of retailers of consumer goods in Grande Florianópolis region, in the Brazilian state of Santa Catarina. Data were collected through a self-managed questionnaire and were analyzed with statistical techniques. Results have shown that multichannel marketing is recent and uses multiple on-line channels. The most commonly used practices are customer satisfaction management, visual merchandising, product/brand portfolio, customer relationship management, and internet/social network monitoring. Significant statistical differences were identified in the promotion/sales practices, alliances/partnerships, product and price policy integration depending on the size of the retailer. The existence of four clusters of multichannel retailers was found: “pioneering”, “experienced”, “less experienced” and “belated”. The study contributed to increasing the knowledge about the subject from the perspective of the retailers as well as to identifying statistical differences in multichannel marketing management practices according to size and clusters in the region studied.